2006
DOI: 10.1242/jcs.02920
|View full text |Cite
|
Sign up to set email alerts
|

Rac1 signalling in theDrosophilalarval cellular immune response

Abstract: The Drosophila larval cellular immune response involves cells (hemocytes) that can be recruited from a hematopoietic organ located behind the brain, as well as a sessile population of cells found just underneath the larval cuticle arranged in a segmental pattern. By using two Rac1 GTPase effector-loop mutants together with epistasis studies, we show that Rac1 requires the Drosophila melanogaster Jun N-terminal kinase Basket (Bsk), as well as stable actin formation to recruit the sessile hemocyte population. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
106
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(113 citation statements)
references
References 45 publications
7
106
0
Order By: Relevance
“…In this study, some of the fly larvae in the Lb treatment exhibited melanized tissues at 72 and 144 h after attack. To be effective, however, melanotic encapsulation should kill the wasp before egg hatching, and it is typically completed by 24-40 h after attack (equivalent to B0 h in our study) (Russo et al, 1996;Williams et al, 2006). These observations suggest that Spiroplasma does not enhance the fly's ability to encapsulate wasp embryos, but improvement of other aspects of immunity cannot be ruled out (e.g., enhancement of cytotoxic products such as reactive oxygen species or intermediates of the melanization cascade; Lemaitre and Hoffmann, 2007).…”
Section: Wasp-killing Mechanismmentioning
confidence: 99%
“…In this study, some of the fly larvae in the Lb treatment exhibited melanized tissues at 72 and 144 h after attack. To be effective, however, melanotic encapsulation should kill the wasp before egg hatching, and it is typically completed by 24-40 h after attack (equivalent to B0 h in our study) (Russo et al, 1996;Williams et al, 2006). These observations suggest that Spiroplasma does not enhance the fly's ability to encapsulate wasp embryos, but improvement of other aspects of immunity cannot be ruled out (e.g., enhancement of cytotoxic products such as reactive oxygen species or intermediates of the melanization cascade; Lemaitre and Hoffmann, 2007).…”
Section: Wasp-killing Mechanismmentioning
confidence: 99%
“…One family of proteins known to be centrally involved in the regulation of cell migration and cell shape change is the Rho GTPases (Rho, Rac, and Cdc42). Recently, two articles have been published showing that both Drosophila Rac GTPase (Rac1 and Rac2) are necessary for proper encapsulation eggs from the parasitoid wasp Leptopilina boulardi (64,65). In Rac2 mutants, the plasmatocytes and lamellocytes recognize and attach to the wasp egg but fail to spread around it.…”
Section: Encapsulationmentioning
confidence: 99%
“…This lack of spreading means septate junctions fail to form, and the capsule fails to melanize. Williams et al (65) showed that Rac1 and the Drosophila JNK (Basket) are also required for proper encapsulation, but the reason is still unknown. Interestingly, it has also been published that the Drosophila ␤ 2 -integrin (known as Myospheroid) is necessary for proper encapsulation of the wasp egg (66).…”
Section: Encapsulationmentioning
confidence: 99%
“…The venom of ISm females, a highly virulent strain against Drosophila melanogaster, contains a RhoGAP protein that is required for parasitism success (12). This factor targets Drosophila lamellocytes, the main capsule-forming hemocytes, and induces changes in their morphology by inactivating the RhoGTPases Rac1 and Rac2, both required for successful encapsulation (13)(14)(15)(16)(17). L. boulardi ISy females differ from ISm females in their ability to suppress immune defenses of both D. melanogaster and Drosophila yakuba hosts but depending on the host resistance genotype (11,18).…”
mentioning
confidence: 99%